1993
DOI: 10.1159/000126555
|View full text |Cite
|
Sign up to set email alerts
|

17β-Estradiol and Progesterone Positively Modulate Spinal Cord Dynorphin: Relevance to the Analgesia of Pregnancy

Abstract: Pregnancy and parturition are associated with opioid-mediated elevations in maternal pain thresholds. This analgesia is subserved by a spinal cord dynorphin/K-opiate receptor system. During gestation, elevated pain thresholds are paralleled by a significant increase in the content of dynorphin (1–17 and 1–8) in the lumbar spinal cord. An additional increment in lumbar dynorphin (1–17) concentration, but not that of dynorphin (1–8), occurs in parturient animals. Simulation of the pregnancy blood concentration p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
31
0
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(37 citation statements)
references
References 19 publications
4
31
0
2
Order By: Relevance
“…There are a number of possible molecular mechanisms via which estrogen might diminish OFQ-induced antinociception, including decreasing the expression of the ORL 1 receptor (Flores et al, 2003) and/or its coupling to G-proteins (for review, see Kelly and Wagner, 1999;Malyala et al, 2005), which would secondarily modify the affinity of OFQ to the ORL 1 receptor. Estrogen receptors (ER␣/ER␤) are present in spinal dorsal horn neurons (Amandusson et al, 1996(Amandusson et al, , 1999Shughrue et al, 1997), and estrogen, in addition to altering the expression of opioid peptides (Medina et al, 1993;Micevych et al, 1997;Amandusson et al, 1999;Micevych and Sinchak, 2001) (for review, see Craft et al, 2004), has also been shown by us and others to alter the expression of the ORL 1 receptor gene and protein in the trigeminal region and the hypothalamus (Sinchak et al, 1997;Flores et al, 2003;Sinchak et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of possible molecular mechanisms via which estrogen might diminish OFQ-induced antinociception, including decreasing the expression of the ORL 1 receptor (Flores et al, 2003) and/or its coupling to G-proteins (for review, see Kelly and Wagner, 1999;Malyala et al, 2005), which would secondarily modify the affinity of OFQ to the ORL 1 receptor. Estrogen receptors (ER␣/ER␤) are present in spinal dorsal horn neurons (Amandusson et al, 1996(Amandusson et al, , 1999Shughrue et al, 1997), and estrogen, in addition to altering the expression of opioid peptides (Medina et al, 1993;Micevych et al, 1997;Amandusson et al, 1999;Micevych and Sinchak, 2001) (for review, see Craft et al, 2004), has also been shown by us and others to alter the expression of the ORL 1 receptor gene and protein in the trigeminal region and the hypothalamus (Sinchak et al, 1997;Flores et al, 2003;Sinchak et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…During late pregnancy and parturition, changes in hormonal and sensory aspects of maternal physiology induce a significant increase in pain threshold [11,15,33,53]. Opioid mechanisms play a pivotal role in the mediation of this effect [23,78], and provide, presumably, the endogenous analgesic substrate(s) for ingested POEF at parturition [45].…”
Section: Discussionmentioning
confidence: 99%
“…Spinal dynorphin-and metenkephalin pathways are activated concomitantly but are subject to individual regulation (Gupta and Gintzler, 2003). As pregnancy progresses, the level of spinal met-enkephalin gradually increases throughout the spinal cord whereas the increase in dynorphin is restricted to the lumbar regions receiving pelvic afferents (Medina et al, 1993). It has been suggested that met-enkephalin therefore is of importance to the basal opioid tone and serves to facilitate spinal dynorphin activity, which is required for antinociception to occur (Gupta and Gintzler, 2003).…”
Section: Estrogen Receptor Neurons and The Endogenous Opioid Systemmentioning
confidence: 99%
“…Even though progesterone receptors have not been detected in the dorsal horn of the spinal cord (Kastrup et al, 1999), the possibility that progesterone also contributes to the effects of estrogen must be considered. Progesterone has indeed been shown to alter the nociceptive effects of estrogens (Drury and Gold, 1978;Kuba et al, 2006) at a spinal level (McCarthy et al, 1990;Medina et al, 1993;Ren et al, 2000) and to regulate nociception-related P2X3-receptor function in dorsal root ganglion neurons (Fan et al, 2011). Pregnancy-induced analgesia requires progesterone to become manifest so this analgesia is not seen in response to estrogens alone (Gintzler and Liu, 2001).…”
Section: Estrogen Receptor Neurons and The Endogenous Opioid Systemmentioning
confidence: 99%